A synergic and compatible microbial-based consortium for biocontrol of Fusarium wilt of tomato - SIDHARTHAN, Venkidusamy Kavi; POTHIRAJ, Govindan; SURYAPRAKASH, Vinayagamoorthy; SINGH, Awani Kumar; AGGARWAL, Rashmi; SHANMUGAM, Veerubommu (Phytopathologia Mediterranea, 2023)
Bioconsortia, based on Chaetomium globosum (isolate CgCG-2), Pseudomonas putida (PpTS-1), Bacillus subtilis (BsS2BC-1), and Trichoderma harzianum (ThS17TH), were designed to develop eco-friendly alternatives for biocontrol of vascular wilt of tomato caused by Fusarium oxysporum f. sp. lycopersici (Fol). In vitro compatibilities of microbes in these consortia were assessed for growth, antagonism, and biocontrol-related gene expression. In these bioassays, the biocontrol isolates had positive interactions for the tested parameters. In pot experiments, seed and soil applications of culture suspensions of five different isolate mixtures were assessed, in comparisons with individual isolates, for efficacy in vascular wilt control after challenge inoculations with Fol under polyhouse conditions. Compared to experimental controls, the biocontrol isolate mixtures reduced vascular wilt incidence and promoted plant growth. PpTS-1 + CgCG-2 + ThS17TH was the most effective microbial consortium, giving 71% reduction of Fusarium wilt incidence compared to non-treated controls. This reduced incidence increased plant growth by 135%. Upregulation of genes encoding for allene oxide cyclase, pathogenesis-related proteins 3, and 5, and β-1,3-glucanase in tomato plants indicated that the reduction in vascular wilt by the consortia could be partly plant-mediated. This study provides new insights into the development of microbial-based consortia for the biocontrol of vascular wilt in tomato.